PEMANFAATAN SAMPAH PLASTIK DENGAN METODE ECOBRICK SEBAGAI UPAYA UNTUK MENCIPTAKAN LINGKUNGAN YANG BERSIH GUNA MENCEGAH RESIKO STUNTING DI KELURAHAN SUMBER AGUNG - Natalina, Natalina; P.Nasoetioen, P.Nasoetioen; Sulastri, Sulastri; Virgiana, Putri Adela; Putri, Voni Egya Janika (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2022)
Stunting in children is a nutritional problem that is a national problem, this is because stunting has a negative impact on human resources in the future. Basic Health Research in 2013 showed that the prevalence of stunting was still 37.2%. The 2016 National Health Survey noted that the prevalence of stunting reached 33.6%, this is an important health problem because stunting is above the 20% threshold. While stunting in children under five is caused by multifactors such as consumption of nutrition during pregnancy, mother's knowledge about nutrition, limited access to services, inadequate access to sanitation and water hygiene. The purpose of this counseling is to increase public awareness, especially children in the environmental area 2 RT 01 Sumber Agung Village, Kemiling District. The method used is counseling in the form of lectures and demonstrations regarding ecobrick products as a call to care for the environment in order to create a clean and healthy environment. The results obtained are that children can understand the importance of keeping the environment clean and healthy by sorting waste properly and having a positive impact on society to reduce plastic waste and make it a livelihood opportunity